2009
DOI: 10.1021/jf9003253
|View full text |Cite
|
Sign up to set email alerts
|

Nontarget Mechanims Involved in Glyphosate Tolerance Found in Canavalia ensiformis Plants

Abstract: A glyphosate-tolerant population of Canavalia ensiformis was collected in a cover crop in citrus orchards in Veracruz (Mexico), where glyphosate had been used for the first time. A susceptible Amaranthus hybridus L. population was collected from a nearby field that had never been treated with glyphosate. Dose-response experiments indicated a glyphosate tolerance ratio [ED(50)(C. ensiformis)/ED(50) (A. hybridus)] of 7.7. The hypothesis of a high level of glyphosate tolerance was provisionally corroborated on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 36 publications
6
20
0
1
Order By: Relevance
“…4). These results are consistent with those of Cruz-Hipolito et al (2009), who found the legume Canavalia ensiformis to be more tolerant to glyphosate than A. hybridus.…”
Section: Absorption and Translocation Assayssupporting
confidence: 92%
See 4 more Smart Citations
“…4). These results are consistent with those of Cruz-Hipolito et al (2009), who found the legume Canavalia ensiformis to be more tolerant to glyphosate than A. hybridus.…”
Section: Absorption and Translocation Assayssupporting
confidence: 92%
“…The data from the shikimic acid assay with leaf segments are given separately for each trial in the experiment. Regression analysis was conducted with the statistical software package Sigma Plot 8.0 (Cruz-Hipolito et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations